Diabetic concentrations of metformin inhibit platelet-mediated ovarian cancer cell progression - Erices, Rafaela (Oncotarget, 2017)
Clinical studies have suggested a survival benefit in ovarian cancer patients with type 2 diabetes mellitus taking metformin, however the mechanism by which diabetic concentrations of metformin could deliver this effect is still poorly understood. Platelets not only represent an important reservoir of growth factors and angiogenic regulators, they are also known to participate in the tumor microenvironment implicated in tumor growth and dissemination. Herein, we investigated if diabetic concentrations of metformin could impinge upon the previously reported observation that platelet induces an increase in the tube forming capacity of endothelial cells (angiogenesis) and upon ovarian cancer cell aggressiveness. We demonstrate that metformin inhibits the increase in angiogenesis brought about by platelets in a mechanism that did not alter endothelial cell migration. In ovarian cancer cell lines and primary cultured cancer cells isolated from the ascitic fluid of ovarian cancer patients, we assessed the effect of combinations of platelets and metformin upon angiogenesis, migration, invasion and cancer sphere formation. The enhancement of each of these parameters by platelets was abrogated by the present of metformin in the vast majority of cancer cell cultures tested. Neither metformin nor platelets altered proliferation; however, metformin inhibited the increase in phosphorylation of focal adhesion kinase induced by platelets. We present the first evidence suggesting that concentrations of metformin present in diabetic patients may reduce the actions of platelets upon both endothelial cells and cancer cell survival and dissemination.